2014
DOI: 10.4018/ijcallt.2014010105
|View full text |Cite
|
Sign up to set email alerts
|

“I Think” in NS and Chinese NNS Spoken English

Abstract: In spoken English, “I think” is a frequently-used chunk. The frequent use of “I think” in the Chinese non-native speakers' (NNSs') speech has been interpreted as being somewhat overused in previous studies, such as Xu and Xu (2007) and Yang and Wei (2005). The same phenomenon is also found in the present study, which is based on a detailed analysis of three corpora: The Spoken English Corpus of Chinese Learners (SECCL), MICASE and ICE-GB. “I think” is over-represented in the Chinese NNSs' speech in SECCL. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
0
3
1
Order By: Relevance
“…Regarding the differences and similarities between HKE and BrE speakers in using ITH in the two types of conversations, HK speakers use ITH more frequently in private conversations as compared to GB speakers, whereas in public conversations, HK speakers use ITH slightly less as compared to GB speakers. This finding is not exactly in line with previous findings, which suggests that Chinese L2 English speakers consistently overuse ITH in their spoken English as compared to NSs (Huang 2011(Huang , 2014Wang, 2007). The present study sheds some light on the influence of speech genre (public vs. private) in the use of ITH among NNSs (HK) and NSs (GB).…”
Section: Conclusion and Discussioncontrasting
confidence: 72%
See 3 more Smart Citations
“…Regarding the differences and similarities between HKE and BrE speakers in using ITH in the two types of conversations, HK speakers use ITH more frequently in private conversations as compared to GB speakers, whereas in public conversations, HK speakers use ITH slightly less as compared to GB speakers. This finding is not exactly in line with previous findings, which suggests that Chinese L2 English speakers consistently overuse ITH in their spoken English as compared to NSs (Huang 2011(Huang , 2014Wang, 2007). The present study sheds some light on the influence of speech genre (public vs. private) in the use of ITH among NNSs (HK) and NSs (GB).…”
Section: Conclusion and Discussioncontrasting
confidence: 72%
“…Baumgarten and House (2010) found that ITH is used differently by native (NSs) and nonnative speakers (NNSs) of English in L1-L1 and L2-L2 interactions in terms of distribution and functional profiles. In particular, Chinese speakers of English have been found to overuse the phrase ITH in both written and oral discourse (Huang, 2011(Huang, , 2014Mei, 2012;Wang, 2007;Wang & Zhu, 2005;Wu et al, 2010;Yang & Wei, 2005). In addition to overall frequency, the position, collocations and functions of ITH also show significant differences in NS and NNS English.…”
Section: Ith As Used By Chinese Speakers Of Englishmentioning
confidence: 99%
See 2 more Smart Citations